1994
DOI: 10.1111/j.1365-2141.1994.tb05013.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IL‐1 and IL‐4 on the Epo‐independent erythroid progenitor in polycythaemia vera

Abstract: Human recombinant interleukin-1 (IL-1) was studied for its effects on the erythroid progenitors from normal subjects and from patients with polycythaemia vera (PV). No supportive effect of IL-1 was noticed on the normal, erythropoietin (Epo) dependent, erythroid burst-forming unit (BFU-E) using peripheral blood or bone marrow. In contrast, the Epo-independent BFU-E from peripheral blood of PV patients could be stimulated significantly. This enhancing effect of IL-1 was not only observed with unsorted but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The results of the present study have shown that the percentage as well as concentration of CD34' cells in peripheral blood are significantly higher in patients with PV than in healthy controls, a finding in accordance with a recent report by de Wolf et al (14). This observation is likely to indicate that patients with PV have a larger circulating pool of peripheral stem cells and/or progenitor cells than normal subjects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study have shown that the percentage as well as concentration of CD34' cells in peripheral blood are significantly higher in patients with PV than in healthy controls, a finding in accordance with a recent report by de Wolf et al (14). This observation is likely to indicate that patients with PV have a larger circulating pool of peripheral stem cells and/or progenitor cells than normal subjects.…”
Section: Discussionsupporting
confidence: 93%
“…The glycophosphoprotein CD34 is expressed on early haematopoietic stem cells and progenitor cells and can be quantitated with an immunological technique (13). Indeed, an increased number of CD34 antigen expressing (CD34+) cells in peripheral blood was observed in a few PV patients investigated (14).…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 In the 1990s, this phenomenon was complemented by the discovery of increased reactivity to other cytokines, such as interleukin 1, interleukin 3, granulocyte macrophage colony-stimulating factor, and insulin-like growth factor 1. 35 , 36 …”
Section: Pathogenesis Of Pv and Potential Therapeutic Targetsmentioning
confidence: 99%